ANALYSIS OF STAKEHOLDER EFFECTS TOWARDS THE CORPORATE SOCIAL RESPONSIBILITY AND THE DECENTRALIZATION AS MODERATING VARIABLE - ., Zulkarnaini; ., Zuarni; ., Fakriah (PEOPLE: International Journal of Social Sciences, 2015)
The existence of external stakeholders which include government regulations, public pressure, environmental organizations / Non Governmental Organization (NGO), mass media will become an integral part, so that the assessment to the company actions have been indicators that is quite important for all parties, including the government in setting policies with their full authority of autonomy. The purpose of this study is to know the effects of external stakeholders on corporate social responsibility of companies in three different areas in the province of Aceh are Banda Aceh, North Aceh and Lhokseumawe. To further refine the analysis concerns the role of local governments, especially regarding autonomy; the study chose decentralization as moderating variable. The analytical tool is used Moderated Regression Analysis (MRA). The sampling method is purposive sampling of stating the respondents. The results have showed that external stakeholders simultaneously significant effect on corporate social responsibility. Partially, only environmental organizations / NGOs did not have a significant effect, but in terms of the interactions that are affected by decentralization, external stakeholders have a negative effect on corporate social responsibility.